Inflammation and Myeloid Cells in Cancer Progression and Metastasis - Deng, Jenying; Fleming, Jason B. (Frontiers in Cell and Developmental Biology, 2022)
To date, the most immunotherapy drugs act upon T cell surface proteins to promote tumoricidal T call activity. However, this approach has to date been unsuccessful in certain solid tumor types including pancreatic, prostate cancer and glioblastoma. Myeloid-related innate immunity can promote tumor progression through direct and indirect effects on T cell activity; improved understanding of this field may provide another therapeutic avenue for patients with these tumors. Myeloid cells can differentiate into both pro-inflammatory and anti-inflammatory mature form depending upon the microenvironment. Tumor-stroma mediate tumor microenvironment (TME) play an important role in regulated myeloid cells function, T cells activity and tumor progression. In this review, we will discuss the relationship between cancer cells and myeloid cells-mediated tumor immune microenvironment to promote cancer progression and immunotherapeutic resistance. Furthermore, we will describe how cytokines and chemokines produced in the tumor microenvironment influence myeloid cells to produce and immunosuppressive environment. Finally, we will comment on the development of immunotherapeutic strategies with respect to myeloid-related innate immunity.